Moritella viscosa Virulence. Extracellular Products and Host-Pathogen Interaction - Bryndís Björnsdóttir 1978- (2011)
Moritella viscosa is the aetiological agent of winter ulcer disease in farmed salmonid fish. The disease has had significant economic effects on the salmon aquaculture industry in the North Atlantic, and continues to cause problems despite the availability of commercial vaccines. Infections also occur in cultured Atlantic cod (Gadus morhua L.). Improved understanding of M. viscosa, its biology, virulence mechanisms and host-pathogen interactions is therefore important in order to fight disease outbreaks and for development of effective treatments against the disease. The main objectives of this study were to examine the virulence mechanisms of M. viscosa, with emphasis on secreted factors and bacterial interactions with its host. In the first part of the study, the virulence properties of extracellular products (ECP) of 22 M. viscosa isolates were evaluated. The in vivo and in vitro virulence of ECPs were screened and several parameters measured. Virulent isolates produced an unidentified lethal factor and the results reflected the proposed significance ECP may have on the development and pathology of winter ulcer disease. Avirulent M. viscosa isolates produced non-lethal ECPs. Cytotoxin production followed host species origin of isolates and may reflect host adaptation in M. viscosa. Successively, the major extracellular caseinase of M. viscosa was isolated and characterized. The caseinase, termed MvP1, was a previously unknown vibriolysin with virulence related activities. The MvP1 peptidase, which was active over a broad temperature range, caused hemorrhages and tissue destruction in salmon and may aid in bacterial invasion and dissemination within the host. Attempts to construct MvP1 negative mutants were unsuccessful and the importance of this peptidase in M. viscosa virulence was therefore not fully determined. For evaluating the ability of M. viscosa to trigger a host immune response, selected M. viscosa antigens were used to stimulate a continuous salmon cell line. Following stimulation, expression of ...